Minuman Surga dan Kontekstualisasinya Terhadap Kesehatan: (Analisis Tematik Qs. Al-Insan, 76:17 Perspektif Wahbah Zuhaili dalam Kitab Tafsirnya Al-Munir) - Abdul Rouf; Samani Samani; Dea Elfatih (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2025)
This study aims to identify and understand the meaning and spiritual implications of the drink of heaven mentioned in QS. Al-Insan 76:17 with a focus on studying the concept of zanjabil in the perspective of interpretation and science according to the context of Islamic teachings. This study is qualitative, the data source is through library research. Data analysis uses thematic analysis methods, descriptive as a stage of studying texts, messages, instructions or information from sources then confirmed with integrated and holistic units towards general conclusions. The results of this study indicate that ginger (zanjabil) is one of the plants listed in the Qur'an, which has medicinal properties and is used as a spice for cooking. According to the book of tafsir al-Munir by Wahbah Zuhaili, ginger (zanjabil) is a drink with a mixture of ginger that comes from the tears of Salsabil which is delicious and easy to swallow which is given to believers in Heaven. Meanwhile, according to science, ginger (zanjabil) has quite a lot of good nutrition, such as essential oils, gingerol, bioactive compounds with anti-inflammatory and antioxidant effects that can reduce cholesterol and heart disease and cancer. Keywords : Zanjabil, Tafsir al-Munir, Science